(untitled) (Texas Journal of Engineering and Technology, 2022)
The aim of the given work is prevention on wind and water erosion and an improvement of quality of ground, as well as increasing the efficiency of pouring water by using demoralized ecological harmless and economic available polymer-polymer complexes (PPC). In last cheats significant successes in making a new class of modified polymeric material, which has allowed to mark new directions in the field of the physicist-chemistries of polymers. PPC are new broad class of polymeric combinations that find a practical application as desperation membranes, coverings, efficient, materials for medical purpose, medicine facilities, in the process of division of albumen and others. Known in the literature PPC on the base of synthetics corboconnection polymers an complementary stature have low level for using them in the agriculture, in consequence of their low biodistruetion and high cost. The rich possibilities presented PPC, can be marked in bid degrees in the process of high tonnage polymers, such as carboxymetilcellulose (CMC), of from the polymer of natural origin and that can come interaction urineformaldehyde resins (UFR). The main values of these products is connected with their low prices and accessibility and possibility of regulation a physicist chemical getting product characteristics. Obvious advantages of large sealed using specified PPC in the agriculture, for instance, for preventing a windy and water erosion of ground, as well as perfecting of its agrophysical characteristics. In the work develop fundamental approaches to making an efficient technology of getting and using the polymer-polymer complex.